Analisis Upaya Optimalisasi Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) dalam Meningkatkan Pendapatan Asli Daerah (PAD) di Kota Tangerang Selatan - Tesa Afliyenti; Ida Matus Silmi; Muhammad Aprizal; Raza adrian ananta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study is motivated by the importance of optimizing the revenue from Rural and Urban Land and Building Tax (PBB-P2) as one of the sources of Regional Original Revenue (PAD) in South Tangerang City. This study aims to analyze the condition of PBB-P2 management, analyze the optimization efforts of PBB-P2 revenue carried out by the local government, and analyze how the optimization of PBB-P2 revenue contributes to increasing Regional Original Revenue (PAD) in South Tangerang City. This study uses a descriptive qualitative approach with data collection techniques through interviews, documentation, and literature studies. The results of the study indicate that the management of PBB-P2 in South Tangerang City has been carried out through various stages, starting from data collection of tax objects, tax determination, to tax collection from taxpayers. Efforts to optimize PBB-P2 revenue are carried out through various policies and programs, such as arrears collection programs (Pentungan), the provision of incentives in the form of discounts and reductions in administrative sanctions, and improvements in tax payment services. The optimization of PBB-P2 revenue plays an important role in increasing Regional Original Revenue (PAD) in South Tangerang City. This study shows that optimizing regional tax revenue requires proper management as well as policy support and public compliance.